KESIAPAN ORANG TUA DALAM MENGAHADAPI PUBERTASPADA ANAK CEREBRAL PALSY TIPE DYPLEGIA - Nursiam, - (2023)
Every child must go through puberty. puberty is a critical period for adolescents. Changes resulting from puberty often lead to deviant behavior. Parents as the primary school for children play an important role in shaping children's behavior. The purpose of this study was to determine the readiness of parents in dealing with Puberty in children with Cerebral Palsy. At SLB ABC YPLAB Lembang, there are students who have problems with Cerebral Palsy and are going through puberty, so they need guidance from their parents regarding puberty. Students are now in elementary school and have shown that they are starting to like the opposite sex. If this case is not known by the parents, they are worried that unwanted things will happen. So the need for parental readiness as one of the efforts or prevention in puberty with the appearance of unwanted child behavior. The method used in this research is a qualitative method. It can be concluded that fathers are more prepared to face their child's puberty than mothers. The child's activity is not only the mother who helps, but the father's role is also needed. As with cleaning up dirt when a child has finished defecating or urinating, fathers do such things to avoid unwanted things. Therefore, it is necessary to have educational knowledge or seminars about puberty in children with special needs, especially children with Diplegia type Cerebral Palsy. With this, it can make it easier for parents to understand puberty in children with Diplegia type Cerebral Palsy.